Subphrenic abscesses: Round table XXVI Uruguayan Congress of Surgery: coordinator Gonzalo Maquieira - Maquieira, Gonzalo; Chavarría, Oscar; Cazabán, Luis A; Ituño, Carlos; Larre Borges, Uruguay; Osorio, Alvaro (Cirugía del Uruguay, 1976)
Classically called subphrenic abscess (S.A) is a collection of pus or pus and gas, located in one of the subphrenic loggia. The collection is not always made up of pus and gas. Another component such as blood, bile, secretions of the digestive tract, hydatid remains, on which infection is added.